2012
DOI: 10.1016/j.jpolmod.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of educational mismatch on private returns to education: An analysis of the Spanish case (1995–2006)

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in:Journal of Policy Modeling 34 (2012) This study examines the effects of educational mismatch on wages in the Spanish labour market since the mid-nineties. First we study the evolution of returns to education and then we estimate returns to education in terms of the match between the worker's schooling and the job requirements. The results indicate that returns to education have declined since the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 35 publications
(37 reference statements)
1
13
0
6
Order By: Relevance
“…This results are supportive of signalling hypothesis that claims the declining return to education is due to the inability of the highly educated to persistently maintain their productivity-unrelated earnings advantage over the less educated (Groot & Oosterbeek, 1994;Spence, 1973). Many evidences supporting the returns for workers fall because they might be dissatisfied with their current job and dropped their productivity level in the firm (Green & Zhu, 2010;Murillo, Rahona-López, & Salinas-Jiménez, 2012;Verhaest & Omey, 2006 For the second phase, 2007-2012, the estimation result in Table 4 showed that the trend of average private returns increased for all certificates except for LCE in 2007-2012. The results indicated that the employers might pay for certificates if they adequately signal worker productivity; that is, if they act as proper sheepskins.…”
Section: Econometric Resultssupporting
confidence: 68%
“…This results are supportive of signalling hypothesis that claims the declining return to education is due to the inability of the highly educated to persistently maintain their productivity-unrelated earnings advantage over the less educated (Groot & Oosterbeek, 1994;Spence, 1973). Many evidences supporting the returns for workers fall because they might be dissatisfied with their current job and dropped their productivity level in the firm (Green & Zhu, 2010;Murillo, Rahona-López, & Salinas-Jiménez, 2012;Verhaest & Omey, 2006 For the second phase, 2007-2012, the estimation result in Table 4 showed that the trend of average private returns increased for all certificates except for LCE in 2007-2012. The results indicated that the employers might pay for certificates if they adequately signal worker productivity; that is, if they act as proper sheepskins.…”
Section: Econometric Resultssupporting
confidence: 68%
“…Although there is a wide literature analysing the impact of overeducation on wages in Spain (see AlbaRamírez, 1993;Murillo et al 2012;Nieto and Ramos, 2013; among others), to our knowledge, no extensive analysis has tested the role of individuals' skill level on educational mismatch focusing on the Spanish case. Participation in the problem-solving domain was optional, and Spain (and other countries) did not participate in it.…”
Section: Research Institute Of Applied Economicsmentioning
confidence: 99%
“…Para una revisión de esta literatura véase, por ejemplo, Hartog (2000) o McGuiness (2006). Estudios recientes para el caso español puede encontrarse en Murillo et al (2012) y nieto y Ramos (2013).…”
Section: Anexosunclassified